Melanocortin 1 Receptor Signaling Regulates Cholesterol Transport in Macrophages. Issue 1 (4th July 2017) - Rinne, Petteri; Rami, Martina; Nuutinen, Salla; Santovito, Donato; van der Vorst, Emiel P.C.; Guillamat-Prats, Raquel; Lyytikäinen, Leo-Pekka; Raitoharju, Emma; Oksala, Niku; Ring, Larisa; Cai, Minying; Hruby, Victor J.; et al.
Abstract : Background: The melanocortin 1 receptor (MC1-R) is expressed by monocytes and macrophages, where it exerts anti-inflammatory actions on stimulation with its natural ligand α-melanocyte–stimulating hormone. The present study was designed to investigate the specific role of MC1-R in the context of atherosclerosis and possible regulatory pathways of MC1-R beyond anti-inflammation. Methods: Human and mouse atherosclerotic samples and primary mouse macrophages were used to study the regulatory functions of MC1-R. The impact of pharmacological MC1-R activation on atherosclerosis was assessed in apolipoprotein E–deficient mice. Results: Characterization of human and mouse atherosclerotic plaques revealed that MC1-R expression localizes in lesional macrophages and is significantly associated with the ATP-binding cassette transporters ABCA1 and ABCG1, which are responsible for initiating reverse cholesterol transport. Using bone marrow–derived macrophages, we observed that α-melanocyte–stimulating hormone and selective MC1-R agonists similarly promoted cholesterol efflux, which is a counterregulatory mechanism against foam cell formation. Mechanistically, MC1-R activation upregulated the levels of ABCA1 and ABCG1. These effects were accompanied by a reduction in cell surface CD36 expression and in cholesterol uptake, further protecting macrophages from excessive lipid accumulation. Conversely, macrophages deficient in functional MC1-R displayed a phenotype with impaired efflux and enhanced uptake of cholesterol. Pharmacological targeting of MC1-R in atherosclerotic apolipoprotein E–deficient mice reduced plasma cholesterol levels and aortic CD36 expression and increased plaque ABCG1 expression and signs of plaque stability. Conclusions: Our findings identify a novel role for MC1-R in macrophage cholesterol transport. Activation of MC1-R confers protection against macrophage foam cell formation through a dual mechanism: It prevents cholesterol uptake while concomitantly promoting ABCA1- and ABCG1-mediated reverse cholesterol transport. Abstract : Supplemental Digital Content is available in the text.